Successful Repair of Congenital Morgagni Hernia and Ventricular Septal Defect via Median Sternotomy in a Patient with Down Syndrome, Anal Atresia, Pectus Carinatum and Congenital Hypothyroidism - Buğra Harmandar; Hande İştar (Çocuk Dergisi)
Here we report a 5-month-old female patient with Down syndrome who was successfully operated on due to congenital Morgagni hernia and ventricular septal defect concomitantly via median sternotomy. Ventricular septal defect was repaired with a polytetrafluoroethylene patch through the right atriotomy using cardiopulmonary bypass, and diaphragmatic hernia was repaired primarily with prolene sutures reinforced with teflon pledgets after excising the diaphragmatic hernia pouch simultaneously. Entire operation was completed via median sternotomy, and transabdominal approach was not required to repair the diaphragmatic hernia. Postoperative course was uneventful.